2020
DOI: 10.5194/acp-20-10807-2020
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of carbonyl compounds around the Arabian Peninsula: overview and model comparison

Abstract: Abstract. Volatile organic compounds (VOCs) were measured around the Arabian Peninsula using a research vessel during the AQABA campaign (Air Quality and Climate Change in the Arabian Basin) from June to August 2017. In this study we examine carbonyl compounds, measured by a proton transfer reaction mass spectrometer (PTR-ToF-MS), and present both a regional concentration distribution and a budget assessment for these key atmospheric species. Among the aliphatic carbonyls, acetone had the highest mixing ratios… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 124 publications
(188 reference statements)
9
35
0
Order By: Relevance
“…Wang et al (2020) reported CH 3 CHO mixing ratios that were up to a factor of 10 higher than predicted by a global chemistry-transport model (EMAC) in the marine boundary layer around the Arabian Peninsula, implying missing sources of CH 3 CHO in remote and polluted regions. Wang et al (2019) also found that models systematically underestimate CH 3 CHO compared to observations, implying a missing source of acetaldehyde in the remote troposphere. This finding was supported by the simultaneous measurement of peracetic acid (which is formed, for example, via the degradation of acetaldehyde in remote environments) with the organic aerosol source of CH 3 CHO also being insufficient to explain the results.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Wang et al (2020) reported CH 3 CHO mixing ratios that were up to a factor of 10 higher than predicted by a global chemistry-transport model (EMAC) in the marine boundary layer around the Arabian Peninsula, implying missing sources of CH 3 CHO in remote and polluted regions. Wang et al (2019) also found that models systematically underestimate CH 3 CHO compared to observations, implying a missing source of acetaldehyde in the remote troposphere. This finding was supported by the simultaneous measurement of peracetic acid (which is formed, for example, via the degradation of acetaldehyde in remote environments) with the organic aerosol source of CH 3 CHO also being insufficient to explain the results.…”
Section: Introductionmentioning
confidence: 87%
“…Global models have recently revealed discrepancies between simulated and measured acetaldehyde concentrations (Millet et al, 2010;Wang et al, 2019;Wang et al, 2020). Wang et al (2020) reported CH 3 CHO mixing ratios that were up to a factor of 10 higher than predicted by a global chemistry-transport model (EMAC) in the marine boundary layer around the Arabian Peninsula, implying missing sources of CH 3 CHO in remote and polluted regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…H 2 O 2 mixing ratios were measured via dual-enzyme detection (modified AEROLASER AL2021, Garmisch-Partenkirchen, Germany) with a total measurement uncertainty of 9 % and a detection limit of 15 ppt v (Hottmann et al, 2020). DMS was measured via proton-transfer-reaction time-of-flight mass spectrometry (PTR-TOF-MS-8000, Ionicon Analytik GmbH, Innsbruck, Austria) with a detection limit of 15 ppt v (Wang et al, 2020;Edtbauer et al, 2020). CH 3 I was measured with a custom-built fast gas chromatography -mass spectrometry system described by Bourtsoukidis et al (2017) with a detection limit of 0.5 ppt v .…”
Section: Observationsmentioning
confidence: 99%
“…Analytik GmbH, Innsbruck, Austria) with a detection limit of 15 ppt v (Wang et al, 2020;Edtbauer et al, 2020). CH 3 I was measured with a custom-built fast gas chromatography -mass spectrometry system described by Bourtsoukidis et al (2017) with a detection limit of 0.5 ppt v .…”
mentioning
confidence: 99%